THE FUNCTION OF PIETY IN LIFE IN THE PERSPECTIVE OF THE QUR'AN - Haikal Fathurrizqi (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
This research examines the function of devotion in life from the perspective of the Qur'an, this research focuses on the elaboration of how devotion that is always commanded to be always carried out by all Servants of Allah subhanahu wataala, whether it has a significant function to the life of human beings who are here in the position of servants, and so that this research is strong, because this order of devotion is commanded by Allah subhanahu wataala, So this research is seen from the perspective of the Qur'an, this research aims to make all humans, especially believers more confident in their devotion to Allah subhanahu wataala, so that what is practiced is in line with what is believed, several studies have been presented, but only limited to interpreting their devotion, while the author here will focus on the function and impact of devotion on human life as a servant, The theories and concepts applied in this study are qualitative research with a literature study approach, the result of this research is the achievement of knowledge for all servants, that how important devotion is in carrying out life in this world.